MENINGKATKAN KINERJA ANGGARAN BERKONSEP VALUE FOR MONEY - Dekeng Setyo Budiarto; Melinda Dwi Puspitasari (Universitas Muria Kudus, 2020)
This study aims to examine the effect of accountability, transparency, supervision, and participation on-budget performance with the concept of value for money in government organizations (OPD) of the Bantul Regency. This study used 90 financial staff as a sample with a purposive sampling method. This research is a quantitative study with data collection through questionnaires. Data were analyzed by multiple linear regression. This study proves that accountability, transparency, supervision, and participation affect budget performance with the concept of value for money